Aboriginal Heroes of the Resistance : from Pemulwuy to Mabo - Newbury,Paul.W; Newbury, Paul W. (Surry Hills, NSW : Action for World Development, 1999)
"Through a series of review essays, this powerful, thought-provoking book explodes the myth of minimal resistance to white invasion and domination. It goes a long way to restoring these Aboriginal heroes to their rightful place in our national consciousness and to the recovery of Aboriginal history. Incorporating findings from the Royal Commission into Aboriginal Deaths in Custody and the High Court Decision on Native Title, this updated edition (first published in 1988) provides signposts for the way to move forward in the ongoing process of reconciliation."--BACK COVER.
Includes index.
Includes bibliographic references.
Keywords: Aboriginal Australians; Aboriginal Australians -- Biography; Government, Resistance to -- Australia